KNOWLEDGE SHARING DAN MOTIVASI BERPRESTASI: FAKTOR PENENTU KINERJA DENGAN PERAN MEDIASI KOMITMEN ORGANISASI - Zega, Arnol Wandra; Hutasuhut, Saidun (NIAGAWAN, 2025)
This study aims to determine the effect of organizational commitment in influencing employee performance at PT. PELINDO Regional 1 in relation to knowledge sharing and achievement motivation. This study uses an associative method with a quantitative approach. The sampling technique used in this study is stratified random sampling. The data of this study were collected by distributing research questionnaires with a differential semantic scale to 120 permanent employees. The data were processed using SPSS.25 and SmartPLS 3.29. The findings of this study are that knowledge sharing and achievement motivation partially have a significant effect on organizational commitment. Furthermore, knowledge sharing and achievement motivation partially have a significant effect on performance. In addition, organizational commitment as a mediator variable is able to mediate the effect of knowledge sharing and achievement motivation on performance. The implications of this study indicate that the application of knowledge sharing and achievement motivation can increase organizational commitment, thereby improving employee performance. This study is expected to provide practical contributions to management strategies in companies to improve employee performance by implementing good knowledge sharing, achievement motivation, and organizational commitment in the work environment.